2009
DOI: 10.3174/ajnr.a1504
|View full text |Cite
|
Sign up to set email alerts
|

The Leptomeningeal “Ivy Sign” on Fluid-Attenuated Inversion Recovery MR Imaging in Moyamoya Disease: A Sign of Decreased Cerebral Vascular Reserve?

Abstract: BACKGROUND AND PURPOSE:Moyamoya disease is an idiopathic occlusive cerebrovascular disorder with abnormal microvascular proliferation. We investigated the clinical utility of leptomeningeal high signal intensity (ivy sign) sometimes seen on fluid-attenuated inversion recovery images in Moyamoya disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
83
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 20 publications
8
83
0
1
Order By: Relevance
“…3,4,11,14,15 Because secondary collateral pathways are presumed to be recruited once primary collaterals at the circle of Postoperative change in rVR in the bypass-established hemisphere. The increased rVR rate is significantly higher on the bypass-established hemisphere (A ) than that on the contralateral hemisphere (B ) (P ϭ .0018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4,11,14,15 Because secondary collateral pathways are presumed to be recruited once primary collaterals at the circle of Postoperative change in rVR in the bypass-established hemisphere. The increased rVR rate is significantly higher on the bypass-established hemisphere (A ) than that on the contralateral hemisphere (B ) (P ϭ .0018).…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies, 1 of which includes the study reported by our group, revealed that the existence of an ivy sign on a FLAIR image in patients with Moyamoya disease is associated with decreased cerebral VR and development of leptomeningeal collaterals. 3,4 In Moyamoya disease, secondary collaterals are well-developed due to failure of primary collaterals. The recruitment of secondary collaterals is required to supply arterial blood to the ischemic area that has impaired cerebral hemodynamics.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…While CT, positron emission tomography, MR perfusion and TCD have all been used to assess leptomeningeal collateral blood flow in a variety of different disorders, the most effective single method to visualize leptomeningeal collateral blood flow in humans remains through angiographic assessment (Mori et al, 2009;Derdeyn et al, 1999;Thurley et al, 2009;Wu et al, 2008). However, a combination of multiple imaging modalities is ideal to gain a greater understanding of blood flow in the ischemic cortex (Bang et al, 2008;Wu et al, 2008;Kim et al, 2009).…”
Section: Clinical Importance Of Leptomeningeal Collateralsmentioning
confidence: 99%
“…For example, Moyamoya disease is a chronic cerebrovascular disorder caused by progressive stenosis or occlusion of the internal carotid artery, leading to headaches, transient ischemic attacks and stroke (Robertson et al, 1997). Due to the longterm occlusive nature of this disease, leptomeningeal arteries become highly developed and have been shown to be a positive indicator of severity of ischemic symptoms (Mori et al, 2009), and are associated with engorged pial networks and slow blood flow (Chung & Park, 2009). Yamauchi et al (2004) investigated the link between the patterns of collateral circulation and the types of infarcts.…”
Section: Clinical Importance Of Leptomeningeal Collateralsmentioning
confidence: 99%